Peranan K.H Anwar dalam Perkembangan Pesantren Nurul Islam Seri Bandung 1932-1959 - syarifuddin syarifuddin; Supriyanto Supriyanto; Ajimiliansyah Ajimiliansyah; Tedi Rizki; Muhammad Fikri (IAIN Syekh Nurjati Cirebon, 2021)
This paper discusses the role of K.H Anwar in the development of the Nurul Islam Seri Bandung (1932). K.H Anwar's discussion regarding his process in building the Nurul Islam Pesantren Seri Bandung, Ogan Ilir, South Sumatra which originated from K.H Anwar's journey to study in various places in Ogan Ilir, Jambi to Mecca and Medina. Furthermore, from the beginning he preached in the village of Seri Bandung and held recitation or cawisan, until he planned to establish a boarding school which was realized in 1932 through a long process because licensing was very strict at that time by the Dutch colonial government. K.H Anwar is a scholar who plays a role in Islamic education in Ogan Ilir district, he has works which later became a reference for use in the Nurul Islam Seri Bandung Islamic boarding school. Pesantren Nurul Islam is one of the oldest Islamic boarding schools in South Sumatra which is currently 92 years old. In this paper, K.H Anwar focuses on building the Islamic Nuru pesantren such as the pesantren curriculum, writing Islamic boarding school books, the rules of the pesantren that he designed and is still being implemented. This paper uses the historical method with the object of research in the development of the Nurul Islam Seri Bandung (1932). The purpose of this research is specifically to examine the role of K.H Anwar in the development of the Nurul Islam Islamic Boarding School Series Bandung 1932-1959. The result of this research is the history of K.H Anwar's role in the development of the Nurul Islam Islamic Boarding School Series Bandung 1932-1959.